Synecology of Cutandia maritma (L.) Barbey, a rare psammophytc species along the Montenegrin Coast (East Adriatc Coast) - Stešević, Danijela; Bubanja, Nada; Caković, Danka; Jogan, Nejc; Luković, Milica; Šilc, Urban (Hacquetia, 2018)
Cutandia maritima is a circum-Mediterranean species that inhabits sandy dunes along the coast line. It is fairly frequent on the western Adriatic coast but fairly rare and possibly even non-native in the east. In Croatia, it was discovered in 1990 in Crnika Bay on the island of Rab, which was considered until 2005 to be the only site on the eastern Adriatic coast from the Gulf of Trieste in the north to Corfu in the south. In 2009, the species was brieﬂy reported for Velika plaža (Long Beach) in Ulcinj (Montenegro) but without details about the habitat type and synecology. Te aim of this paper is thus to provide a deeper insight into the ecology and synecology of C. maritima in the eastern Adriatic part of the distribution area. On Velika plaža in Ulcinj, the species was found along the whole sea-inland gradient of sand dunes, in various types of vegetation: [1210] – annual vegetation of drift lines, [2110] – embryonic shifting dunes, [2120] – shifting dunes with Ammophila arenaria (white dunes), [2220] – dunes with Euphorbia terracina, [2130*] – fxed coastal dunes with herbaceous vegetation (grey dunes), and also [2190] – humid dune slacks.